2017
DOI: 10.1039/c7mt00039a
|View full text |Cite
|
Sign up to set email alerts
|

Analogues of desferrioxamine B designed to attenuate iron-mediated neurodegeneration: synthesis, characterisation and activity in the MPTP-mouse model of Parkinson's disease

Abstract: Parkinson's disease (PD) is a neurodegenerative disorder characterised by the death of dopaminergic neurons in the substantia nigra pars compacta (SNpc) region of the brain and formation of α-synuclein-containing intracellular inclusions. Excess intraneuronal iron in the SNpc increases reactive oxygen species (ROS), which identifies removing iron as a possible therapeutic strategy. Desferrioxamine B (DFOB, 1) is an iron chelator produced by bacteria. Its high Fe(iii) affinity, water solubility and low chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 69 publications
0
23
0
Order By: Relevance
“…The authors concluded that there was a need to develop safe and effective chelators for therapeutic use. While the aim of this study was to reduce aluminum levels in AD patients, deferoxamine has the capacity to bind several metals such as zinc, copper and iron; the affinity for iron is six times higher than that of aluminum (Gotsbacher et al, 2017 ), therefore it is postulated that the effects seen in the study may have been a result of iron chelation. Indeed, targeting iron has been reported to have therapeutic benefits in clinical trials of PD patients (tau is also disrupted in PD and in animal models of PD).…”
Section: Iron Metabolismmentioning
confidence: 96%
“…The authors concluded that there was a need to develop safe and effective chelators for therapeutic use. While the aim of this study was to reduce aluminum levels in AD patients, deferoxamine has the capacity to bind several metals such as zinc, copper and iron; the affinity for iron is six times higher than that of aluminum (Gotsbacher et al, 2017 ), therefore it is postulated that the effects seen in the study may have been a result of iron chelation. Indeed, targeting iron has been reported to have therapeutic benefits in clinical trials of PD patients (tau is also disrupted in PD and in animal models of PD).…”
Section: Iron Metabolismmentioning
confidence: 96%
“…Although both radiopharmaceuticals had very similar blood clearance profiles, animals injected with the [ 89 Zr]Zr- D FO*- p -Phe-NCS-trastuzumab demonstrated significantly lower radioactivity levels in liver, spleen, and bone tissue, which was corroborated by small animal PET/CT studies in the same xenograft model. The development of 20 represents a significant achievement in 89 Zr chelator design, and since recent efforts to improve the water solubility of this ligand have been successful the radiopharmaceutical community anxiously awaits its evaluation in a clinical setting [ 109 , 110 , 111 ].…”
Section: The Rationale For New Zirconium-89 Chelation Strategiesmentioning
confidence: 99%
“…Consistent with that, N-acetyl-l-cysteine (NAC), an antioxidant, which could decrease iron levels, showed neuroprotective effect in PD models [ 61 ]. Moreover, desferrioxamine (DFO) and VAR10303 (VAR), two kinds of iron chelator, reduced the ROS and rescued the MPTP induced PD mouse phenotypes [ 62 , 63 ]. Collectively, iron can also contribute to pathogenesis of PD via aggravating ROS production.…”
Section: Ros and Pd-associated Factorsmentioning
confidence: 99%